Tinjauan Yuridis Pendaftaran Perjanjian Kawin di Kota Serang Dalam Perspektif Undang-Undang Nomor 16 Tahun 2019 Tentang Perubahan Atas Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan dan Putusan Mahkamah Konstitusi Nomor 69/PUU-XIII/2015: Tinjauan Yuridis Pendaftaran Perjanjian Kawin di Kota Serang Dalam Perspektif Undang-Undang Nomor 16 Tahun 2019 Tentang Perubahan Atas Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan dan Putusan Mahkamah Konstitusi Nomor 69/PUU-XIII/2015 - Ayu Putri Lestari (CV Rewang Rencang, 2025)
This research discusses the absence of severance pay provisions in the Collective Labor Agreement (CLA) between workers and employers, as well as its legal implications, with a focus on the Decision of the Industrial Relations Court of Yogyakarta No. 19/Pdt.Sus-PHI/2022/PN Yyk. Severance pay is a right granted to workers who experience termination of employment (dismissal) not due to serious misconduct. However, in practice, many CLAs do not explicitly include such provisions. This raises issues when termination occurs, particularly concerning legal certainty and the protection of workers' rights. This study discusses the registration of marriage agreements in the city of Serang from the perspective of law number 16 of 2019 concerning amendments to law number 1 of 1974 concerning marriage and the Constitutional Court Decision number 69/PUU-XIII/2015. A marriage agreement is a written agreement between a prospective husband and wife made before or during the marriage period to regulate the separation of property, responsibilities, and rights of each party. This Agreement is valid if it is notarized and registered in accordance with the provisions of applicable law. The purpose of this study is to find out and analyze the process of registering marriage agreements in the city of Serang before and after the Constitutional Court Decision Number 69/PUU-XIII/2015 and to find out and analyze the legal consequences if the marriage agreement is not registered in accordance with the Constitutional Court Decision Number 69/PUU-XIII/2015. In this method, the approach used is normative juridical In this study, the researcher also uses the approach, the statute approach, the conceptual approach, the case approach, In this study, the researcher also uses Primary legal materials, secondary legal materials and Tertiary legal materials. The data collection technique used in this study is by literature study, qualitative descriptive data analysis procedures. The results of the study show that marriage agreements made before marriage must be registered before the date of marriage registration in order to have legal force, while marriage agreements made after marriage must be ratified and must also be registered in order to bind third parties. Registration functions an important function in ensuring legal certainty, transparency of assets, and legal protection for the parties. In conclusion, the registration of marriage agreements, both before and after the Constitutional Court Decision Number 69/PUU-XIII/2015, has an important role in providing legal certainty, binding power, and legal protection for husband and wife and third parties. Without official registration, the agreement is only valid privately and has the potential to cause legal uncertainty, third-party losses, and abandonment in divorce, inheritance, or mixed marriage cases. Registration is not just an administrative formality, but an essential requirement for the agreement to be valid and recognized in the legal system and state administration